Kajian Pustaka: Standarisasi Umbi Bawang Dayak (Eleutherine bulbosa (Mill.) dan Bawang Putih (Allium cepa L.) - Sepbrilla Ananda Kusriadi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Eleutherine bulbosa (Mill.) and Allium cepa L. (including garlic and onion peel) are medicinal plants that have long been traditionally used to treat cancer, diabetes, hypertension, infectious diseases, and inflammation. Recent scientific studies emphasize the importance of extract standardization to ensure consistent quality, safety, and efficacy. Standardization includes specific parameters—such as organoleptic identification, water- and ethanol-soluble extract values, phytochemical profiles, and determination of marker compounds—and nonspecific parameters such as moisture content, loss on drying, total ash, and acid-insoluble ash. Ethanol extract of E. bulbosa showed moisture and drying loss values below 10%, total flavonoid content of around 1.2%, and positive phytochemical tests for alkaloids, flavonoids, saponins, and quinones. Onion peel extract contains a high flavonoid content (7.84 mg QE/g) with moderate antioxidant capacity (DPPH IC₅₀ 152.65 µg/mL), while fermented garlic (black garlic) contains more than 12% polyphenols and more than 2% flavonoids, as well as a high level of S-allyl-L-cysteine (SAC) as a stable bioactive compound. The pharmacological activities of these standardized extracts include strong antioxidant effects, α-glucosidase inhibition for antidiabetic activity, induction of apoptosis and anti-angiogenesis as anticancer potential, membrane disruption and enzyme inhibition for antimicrobial activity, as well as COX/LOX modulation for anti-inflammatory effects. These activities are directly correlated with the secondary metabolite composition of each material. With their phytochemical richness and diverse biological activities, E. bulbosa and A. cepa have great potential as raw materials for standardized herbal products. Further in vivo studies and clinical trials are needed to validate their therapeutic efficacy and to support the development of evidence-based phytopharmaceuticals.